PENGGUNAAN MEDIA KARTU BERGAMBAR DALAM MENINGKATKAN LITERASI MEMBACA ANAK USIA 5-6 TAHUN: STUDI DESKRIPTIF KUALITATIF DI TK AISYIYAH BUSTANUL ATHFAL PANONGAN 1 - Rokhimah; Maya Lestari (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Reading literacy is a basic skill for early childhood as a foundation for language and cognitive development. Children aged 5–6 years are in the early reading stage and therefore require stimulation through engaging and developmentally appropriate learning media. Picture cards combine visual and textual elements to help children recognize letters, words, and simple sentences. This study aims to determine strategies for using picture cards, analyze their effectiveness in improving reading literacy, and identify supporting and inhibiting factors at Aisyiyah Bustanul Athfal Panongan 1 Kindergarten. The study used a descriptive qualitative approach with 22 children in Group B and teachers and the principal as informants. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model and triangulation. The results showed that picture cards effectively increased children's interest and reading literacy, as evidenced by improvements in letter recognition, simple word reading, and understanding of meaning. Supporting factors included teacher creativity and children's interests, while inhibiting factors included limited media and differences in children's abilities.